2015
DOI: 10.1242/jeb.111922
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on leg kinematics in sprinting tarantulas (Aphonopelma hentzi): high speed may limit hydraulic joint actuation

Abstract: Tarantulas extend the femur-patella ( proximal) and tibia-metatarsal (distal) joints of their legs hydraulically. Because these two hydraulically actuated joints are positioned in series, hemolymph flow within each leg is expected to mechanically couple the movement of the joints. In the current study, we tested two hypotheses: (1) at lower temperatures, movement of the two in-series hydraulic joints within a leg will be less coupled because of increased hemolymph viscosity slowing hemolymph flow; and (2) at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…Spider locomotion is particularly sensitive to temperature variations (Booster et al, 2015). The room in which the experiment was conducted was heated and air conditioned.…”
Section: Data Collectionmentioning
confidence: 99%
“…Spider locomotion is particularly sensitive to temperature variations (Booster et al, 2015). The room in which the experiment was conducted was heated and air conditioned.…”
Section: Data Collectionmentioning
confidence: 99%
“…As for orb-weavers, the fact that an ambusher spider waits for its prey can result in a difference between the body temperature of the predator and the prey thus being advantageous for the flying insect. Booster et al (2015) hypothesized that at lower temperatures, the movement of the spider leg joints could be less coupled because of increased hemolymph viscosity thus slowing the flow of hemolymph, and demonstrated that at high temperature the spiders ran the fastest with the highest stride Fig. 4.…”
Section: Bioecological Interpretation Of the Effect Of Temperature Onmentioning
confidence: 99%
“…In E. weijenberghi, the F S resulted to be the main determinant factor of the speed changes, at least within the limited range we studied. This result agrees with previous findings in other tarantulas (Anderson & Prestwich, 1985;Booster et al, 2015).…”
Section: Gait Patternsupporting
confidence: 94%